2019
DOI: 10.1038/s41467-019-09712-x
|View full text |Cite
|
Sign up to set email alerts
|

Excessive miR-25-3p maturation via N6-methyladenosine stimulated by cigarette smoke promotes pancreatic cancer progression

Abstract: N 6 -methyladenosine (m 6 A) modification is an important mechanism in miRNA processing and maturation, but the role of its aberrant regulation in human diseases remained unclear. Here, we demonstrate that oncogenic primary microRNA-25 (miR-25) in pancreatic duct epithelial cells can be excessively maturated by cigarette smoke condensate (CSC) via enhanced m 6 A modification that is mediated by NF-κB associated protein (NKAP). This modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
241
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(261 citation statements)
references
References 70 publications
3
241
1
Order By: Relevance
“…Another study revealed the role of m6A in miRNA processing, and the role of miR-25-3p was recently reported. In this study, Zang indicated the effect of cigarette smoking on m6A-modified miR-25-3p maturation in pancreatic ductal adenocarcinoma [76]. This research showed that the specific regulatory mechanism of METTL3 upregulation caused by cigarette smoking involves the epigenetic regulation of the METTL3 promoter.…”
Section: M6a Modifications and Noncoding Rnasmentioning
confidence: 79%
See 1 more Smart Citation
“…Another study revealed the role of m6A in miRNA processing, and the role of miR-25-3p was recently reported. In this study, Zang indicated the effect of cigarette smoking on m6A-modified miR-25-3p maturation in pancreatic ductal adenocarcinoma [76]. This research showed that the specific regulatory mechanism of METTL3 upregulation caused by cigarette smoking involves the epigenetic regulation of the METTL3 promoter.…”
Section: M6a Modifications and Noncoding Rnasmentioning
confidence: 79%
“…In this case, as a protein molecule, DGCR8 has potential as a therapeutic target. Another study reported that the upregulation of METTL3 caused an increase in miR-25-3p and that miR-25-3p could promote the expression of its target protein PHLPP2 to promote pancreatic ductal adenocarcinoma occurrence [76]. Similar to DGCR8, the protein PHLPP2 also shows potential for use in targeted therapy.…”
Section: Potential Clinical Application Of Regulatory Mechanisms Betwmentioning
confidence: 99%
“…In this study, our results support this. 32 Due to the strong connection between DNA methylation and pain processes, 33 we therefore proposed that DNA methylation might be an important mechanism by which METTL3 expression is regulated by pain. To our knowledge, this is the first study on METTL3-mediated m 6 A modification in miRNA processing in pain research.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke condensate promotes m6A, thus contributing to maturation of oncogene miR-25-3p in pancreatic tumor. MiR-25-3p inhibits PH domain leucine-rich repeat protein phosphatase 2 (PHLPP2), leading to the activation of oncogenic AKT-p70S6K signaling [135].…”
Section: M6a Functions As a Tumor Promoter M6a Promotes Expression Ofmentioning
confidence: 99%